What makes a good label? : the effect of wine label design on product evaluation and purchasing behaviour : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Jaud, David Alexandre (Massey University, 2018)
Companies spend billions annually on packaging and labelling, yet little is known about how and why specific features of package design influence consumer responses. This thesis identifies, across two projects, what wine label elements or themes should be used, where and when. First, while the use of fantasy themes is increasing across product categories, it is unclear how consumers react to fantasy labels. Across five studies, the results unite seemingly contradicting theories predicting the effects of fantasy labels on product evaluation and purchasing behaviour by uncovering an important boundary condition: product quality signal, in line with the principle of hedonic dominance. The results suggest that for low quality products, fantasy labels backfire (consistent with research on metacognition). For products average in quality, fantasy and non-fantasy labels do not differ in their performance. Yet, in the presence of a high quality signal, fantasy labels impact product evaluation and purchasing behaviour positively. This positive effect is sequentially driven by the evocation of the imaginary and affect, in line with research on mental simulation. Second, it is unclear to what extent elements of wine label design affect sales relative to other marketing mix effects. Specifically, we use wine transactional data for 127 SKUs across two liquor stores in New Zealand, covering 105 weeks. The findings suggest that some specific label elements have strong effects on sales. Specifically, extra text, as a quality cue, has the strongest positive effect. Overall, after price, the combination of image(s) and extra text has the strongest (negative) effect on sales. In line with research on processing fluency, this research also shows whether and when to use simple versus complex elements (typeface, label structure, mode of information). This thesis has important implications for wine companies and retailers.
Keywords: Wine labels; Design; Wine; Marketing; Consumer behavior; Dean's List of Exceptional Theses; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies